MEWUJUDKAN KEMANDIRIAN EKONOMI MELALUI PEMBERDAYAAN IBU RUMAH TANGGA DENGAN KETRAMPILAN PEMBUATAN SABUN CUCI PIRING DAN MENGHITUNG HPP - W Nurhidayati; Rahoyo; DC Kuswardhani; Nunik Kusnilawati (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this community service activity is to empower women in the Purwoyoso village. This empowerment is able to improve the economic condition of the family. through innovative activities, enabling them to learn various skills to help increase income for women in Purwoyoso sub-district, The method used in this community service activity is to provide direct training with tutorials in the field by teaching making dish soap and calculating HPP (Cost of Production). The results of the service are expected that mothers have skills in making dish soap and calculating HPP so that they can determine the price of goods when sold. With skills in making dish soap, mothers can produce which can later be used alone or sold so that additional income can be obtained.